2010
DOI: 10.1038/bmt.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ cell dose and establishment of full donor chimerism at day +100 are important factors for survival with reduced-intensity conditioning with fludarabine and melphalan before allogeneic hematopoietic SCT for hematologic malignancies

Abstract: The combination of fludarabine and melphalan as a reduced-intensity conditioning (RIC) regimen extends allogeneic hematopoietic SCT (HSCT) as a therapeutic option for elderly or frail patients with relapsed, refractory or other high-risk hematologic malignancies. Whether any modifiable factors exist that could improve survival before or immediately after HSCT is unknown. We reviewed the medical records of the first 50 patients at our institution to undergo fludarabine/melphalan RIC from September 2000 to Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Although Pérez‐Simón et al and Tsirigotis et al reported that the infusion of high doses of CD34+ cells did not have an impact on OS and EFS, we found that the infusion of ≥5 × 10 6 kg −1 CD34+ cells improves OS, without the effect on EFS; in this regard, it is important to note that 123 of 138 patients in our group had a high‐risk, clinically advanced disease status at the time of transplantation. Our results then confirm the findings in a recent study of 50 patients receiving a HSCT after RIC including melphalan and fludarabine, in which a CD34+ cell dose ≥5.5 × 10 6 kg −1 predicted a higher OS . In this respect, we have previously shown that the CD34+ cell content of an apheresis graft remains the single best parameter to predict neutrophil and platelet recovery after HSCT and that flow cytometry determination of additional CD molecules, in particular CD133, offers no additional benefit or information, although apheresis product composition varies due to phenomena like preferential intra‐apheresis recruitment of less lineage‐committed hematoprogenitors, including CD34+/CD133+ stem cells , which in ex vivo experiments have a superior bone marrow repopulation potential; however, this did not lead to faster HSCT recovery times .…”
Section: Discussionsupporting
confidence: 89%
“…Although Pérez‐Simón et al and Tsirigotis et al reported that the infusion of high doses of CD34+ cells did not have an impact on OS and EFS, we found that the infusion of ≥5 × 10 6 kg −1 CD34+ cells improves OS, without the effect on EFS; in this regard, it is important to note that 123 of 138 patients in our group had a high‐risk, clinically advanced disease status at the time of transplantation. Our results then confirm the findings in a recent study of 50 patients receiving a HSCT after RIC including melphalan and fludarabine, in which a CD34+ cell dose ≥5.5 × 10 6 kg −1 predicted a higher OS . In this respect, we have previously shown that the CD34+ cell content of an apheresis graft remains the single best parameter to predict neutrophil and platelet recovery after HSCT and that flow cytometry determination of additional CD molecules, in particular CD133, offers no additional benefit or information, although apheresis product composition varies due to phenomena like preferential intra‐apheresis recruitment of less lineage‐committed hematoprogenitors, including CD34+/CD133+ stem cells , which in ex vivo experiments have a superior bone marrow repopulation potential; however, this did not lead to faster HSCT recovery times .…”
Section: Discussionsupporting
confidence: 89%
“…Data on total donor cell chimerism are especially scanty and discordant, as most studies have focused on donor T-cell chimerism. Two small studies found no association of low total donor cell chimerism with outcomes 2,3 , while other small studies, with varying chimerism thresholds and assessment time-points, described an association with 4-week relapse risk 4 or impaired survival 5,6 . Several small studies have also described an association of donor T-cell chimerism with impaired RIC HSCT outcomes.…”
Section: Introductionmentioning
confidence: 95%
“…In allogeneic stem cell transplantation, several day 100 prognostic factors have been studied to predict clinical outcomes including day 100 absolute lymphocyte count (ALC) [1, 2], day 100 absolute monocyte count (AMC) [1, 2], day 100 platelet count [3], graft-versus-host disease [4], and day 100 full donor chimerism [5]. In autologous stem cell transplantation, multiple myeloma documented minimal residual disease at day 100 was associated with inferior prognosis [6, 7] However, prognostic factors to assess prognosis for classical Hodgkin's lymphoma (cHL) achieving a complete remission at day 100 postautologous peripheral blood hematopoietic stem cell transplantation (APBHSCT) have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%